Large linear anhysteretic magnetoelectric voltage coefficients in CoFe2O4/polyvinylidene fluoride 0-3 nanocomposites - Martins, P. (2013)
Free-standing flexible magnetoelectric 0-3 composite films comprising CoFe2O4 (CFO) non-spherical ferromagnetic nanoparticles with strong magnetic anisotropy in soft polyvinylidene fluoride (PVDF) matrices with significant void ratios have been prepared at low temperatures by solvent casting, melt crystallization and mechanical stretching. Magnetoelectric voltage coefficients increase linearly with applied dc magnetic field bias up to 5 kOe. At this field, a maximum magnetoelectric voltage coefficient of 11.2 mV cm 1 Oe 1 was obtained for samples with 10 wt. % ferrite at ~50 kHz resonance. The observed linear magnetoelectric response is attributed to a linear gradient of magnetostriction with respect to magnetic field for H ≤ 5 kOe.